HIRAEA CUNEATA, H. MACROPHYLLA, AND FOUR NEW SPECIES CONFUSED WITH THEM: H. HATSCHBACHII, H. OCCHIONII, H. REITZII, AND H. RESTINGAE (MALPIGHIACEAE) - Anderson, C. (Edinburgh Journal of Botany, 2014)
Specimens of Hiraea (Malpighiaceae) from the Brazilian states of eastern Minas Gerais, Rio de Janeiro, Paraná, and Santa Catarina that had been determined as H. cuneata Griseb. and H. wiedeana A.Juss. were found to include four undescribed species. The assemblage traditionally named Hiraea cuneata includes, in addition to H. cuneata (Minas Gerais, Rio de Janeiro), two novelties: H. hatschbachii C.E.Anderson (Paraná) and H. occhionii C.E.Anderson (Rio de Janeiro). The gatherings labelled Hiraea wiedeana comprise specimens of H. reitzii C.E.Anderson (Paraná, Santa Catarina) and H. restingae C.E.Anderson (Rio de Janeiro), here newly described, and of H. macrophylla (Colla) P.L.R.Moraes & Guglielmone (Rio de Janeiro), the earlier and correct name for the species also known as H. wiedeana. In all, the flowers are borne in a single 4-flowered umbel instead of a compound arrangement, as is often characteristic of other species of Hiraea. Specimens assigned to Hiraea cuneata have the laminas abaxially sericeous initially but glabrous at maturity. In those assigned to Hiraea wiedeana the laminas are abaxially velutinous (eventually glabrescent in H. restingae). Full descriptions and synonymies are supplied, and all species are illustrated.
Keywords: Brazil; Hiraea; Malpighiaceae; new species